(untitled) (Lingue e culture dei media, 2017)
Per ricordare Tullio De Mauro all’atto di uscita di questa nuova rivista, si richiama il suo apporto allo studio della lingua dei media, proponendo un’analisi riassuntiva dei momenti in cui si è articolato l’approccio critico-interpretativo alle scelte espressive dei moderni strumenti di comunicazione. Nel contributo si sottolinea la centralità di questa tematica nella ricerca complessiva di De Mauro e nella sua lettura dei fatti linguistici dell’Italia moderna e contemporanea. Upon the publishing of this new journal, in memory of Tullio De Mauro, we recall his contribution to media language studies, with a summary analysis of the different stages through which the critical-interpretative approach to the selection of forms of expression related to modern means of communication has been developed.. The contribution underlines the importance of this aspect throughout De Mauro’s research and in his interpretation of linguistical facts in modern and contemporary Italy.